Antimicrobial Susceptibility Testing of Antimicrobial Peptides to Better Predict Efficacy - Mercer, Derry K.; Torres, Marcelo D. T.; Duay, Searle S.; Lovie, Emma; Simpson, Laura; von Köckritz-Blickwede, Maren; de la Fuente-Nunez, Cesar; O'Neil, Deborah A.; Angeles-Boza, Alfredo M. (Frontiers in Cellular and Infection Microbiology, 2020)
During the development of antimicrobial peptides (AMP) as potential therapeutics, antimicrobial susceptibility testing (AST) stands as an essential part of the process in identification and optimisation of candidate AMP. Standard methods for AST, developed almost 60 years ago for testing conventional antibiotics, are not necessarily fit for purpose when it comes to determining the susceptibility of microorganisms to AMP. Without careful consideration of the parameters comprising AST we run the risk of failing to identify novel antimicrobials at a time when antimicrobial resistance (AMR) is leading us towards a post-antibiotic era. More physiologically/clinically relevant AST will allow us to better determine the preclinical activity of drug candidates and allow the identification of lead compounds. An important consideration is the efficacy of AMP in biological matrices replicating sites of infection, e. g. blood/plasma/serum, lung bronchiolar lavage fluid/sputum, urine, biofilms, etc., as this will likely be more predictive of clinical efficacy. Additionally, specific AST for different target microorganisms may help to better predict efficacy of AMP in specific infections. In this manuscript, we describe what we believe are the key considerations for AST of AMP and hope that this information can better guide the preclinical development of AMP towards becoming a new generation of urgently needed antimicrobials.